Respuesta :

Answer:

-2

Step-by-step explanation:

f(t) = t^2 – 2t – 2

To find f(0), replace t with 0 in the expression and evaluate the expression.

f(0) = 0^2 – 2(0) – 2

f(0) = -2

0 = t

We know this because 0 replaced t in the parenthesis next to F !

The question is just asking you to plug in 0 where ever t is!

Let's do it

[tex]f(0) = 0^{2} - 2(0) - 2[/tex]

solve

[tex]0^{2} = 0 \\2 ( 0 ) = 0[/tex]

so, this is what we have left!

[tex]f(0) = 0 - 0 - 2[/tex]

We have our answer!

[tex]f (0) = -2[/tex]